Fans & ventilation a practical guide - Cory, W. T. W., 1934-
The practical reference book and guide to fans, ventilation and ancillary equipment with a comprehensive buyers? guide to worldwide manufacturers and suppliers. Bill Cory, well-known throughout the fans and ventilation industry, has produced a comprehensive, practical reference with a broad scope: types of fans, how and why they work, ductwork, performance standards, testing, stressing, shafts and bearings. With advances in technology, manufacturers have had to continually improve the performance and efficiency of fans and ventilation systems; as a result, improvements that once seemed impossi.